PENGEMBANGAN MEDIA AUDIO-VISUAL MATERI NOTASI BALOK DI EKSTRAKURIKULER SENI MUSIK SMA NEGERI 2 MEMPAWAH HILIR - Sulistio, Agus; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstactThe type of research is Research and Development (R & D) in stage 2 in which the researcher did not make product design through research but only made or tested the effectiveness, efficiency and practicality of the use of existing products. The steps used in developing this instructional media use the steps of Borg and Gaal (2003) that have been simplified by Tim Pusjaliktnov (2008). This media had been validated by the material and media experts and small-scale field testing phase. Material and media experts stated that this media was suitable to be applied as a medium of learning material of beam notation. The average score of the material experts is 3, which is in the category of